(–)-Epigallocatechin-3-gallate induces apoptosis and differentiation in leukaemia by targeting reactive oxygen species and PIN1 - Della Via, Fernanda Isabel (Sci Rep, 2021)
(–)-Epigallocatechin-3-gallate (EGCG), the major active polyphenol extracted from green tea, has been shown to induce apoptosis and inhibit cell proliferation, cell invasion, angiogenesis and metastasis. Herein, we evaluated the in vivo effects of EGCG in acute myeloid leukaemia (AML) using an acute promyelocytic leukaemia (APL) experimental model (PML/RARα). Haematological analysis revealed that EGCG treatment reversed leucocytosis, anaemia and thrombocytopenia, and prolonged survival of PML/RARα mice. Notably, EGCG reduced leukaemia immature cells and promyelocytes in the bone marrow while increasing mature myeloid cells, possibly due to apoptosis increase and cell differentiation. The reduction of promyelocytes and neutrophils/monocytes increase detected in the peripheral blood, in addition to the increased percentage of bone marrow cells with aggregated promyelocytic leukaemia (PML) bodies staining and decreased expression of PML-RAR oncoprotein corroborates our results. In addition, EGCG increased expression of neutrophil differentiation markers such as CD11b, CD14, CD15 and CD66 in NB4 cells; and the combination of all-trans retinoic acid (ATRA) plus EGCG yield higher increase the expression of CD15 marker. These findings could be explained by a decrease of peptidyl-prolyl isomerase NIMA-interacting 1 (PIN1) expression and reactive oxygen species (ROS) increase. EGCG also decreased expression of substrate oncoproteins for PIN1 (including cyclin D1, NF-κB p65, c-MYC, and AKT) and 67 kDa laminin receptor (67LR) in the bone marrow cells. Moreover, EGCG showed inhibition of ROS production in NB4 cells in the presence of N-acetyl-L-cysteine (NAC), as well as a partial blockage of neutrophil differentiation and apoptosis, indicating that EGCG-activities involve/or are in response of oxidative stress. Furthermore, apoptosis of spleen cells was supported by increasing expression of BAD and BAX, parallel to BCL-2 and c-MYC decrease. The reduction of spleen weights of PML/RARα mice, as well as apoptosis induced by EGCG in NB4 cells in a dose-dependent manner confirms this assumption. Our results support further evaluation of EGCG in clinical trials for AML, since EGCG could represent a promising option for AML patient ineligible for current mainstay treatments.